2012
DOI: 10.3390/molecules171214637
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiradical/Antioxidant Activities of Caffeic Acid Phenethyl Ester and Its Related Propionic, Acetic, and Benzoic Acid Analoguesc

Abstract: Caffeic acid phenethyl ester (CAPE) is a bioactive component isolated from propolis. A series of CAPE analogues was synthesized and their antiradical/antioxidant effects analyzed. The effect of the presence of the double bond and of the conjugated system on the antioxidant effect is evaluated with the analogues obtained from 3-(3,4-dihydroxyphenyl) propanoic acid. Those obtained from 2-(3,4-dihydroxyphenyl) acetic acid and 3,4-dihydroxybenzoic acid allow the evaluation of the effect of the presence of two carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 29 publications
(37 reference statements)
0
33
0
1
Order By: Relevance
“…Most of the protective effects were observed at a concentration of 250 μM, whereas the protection against the oxidative damage was obtained with 100 μM ES. It is possible that the protective effect of ES against lipid peroxidation and the drop in antioxidant enzyme activities may rely on its potent free radical scavenging capacities [19,23,24], preventing the oxidative attacks to lipids (Fig. 4D) and proteins and thus conserving antioxidant enzyme activities ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the protective effects were observed at a concentration of 250 μM, whereas the protection against the oxidative damage was obtained with 100 μM ES. It is possible that the protective effect of ES against lipid peroxidation and the drop in antioxidant enzyme activities may rely on its potent free radical scavenging capacities [19,23,24], preventing the oxidative attacks to lipids (Fig. 4D) and proteins and thus conserving antioxidant enzyme activities ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Colonic microbiota can degrade flavonoids, generating a large number of metabolites that can be absorbed and exert biological effects in the body, such as antioxidant, antimicrobial and anti-inflammatory activities, among others [14]. The major microbial metabolite of QUE and its glycosylated derivatives is ES (homoprotocatechuic acid) [15][16][17][18][19][20][21][22], which also possesses potent antioxidant properties. It has been shown that this compound has the highest free radical scavenging activity among several flavonoid metabolites tested in vitro, and that it may reduce plasma lipid peroxidation in vivo [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Caffeic acid and some of its esters and amides derivatives exhibit a broad spectrum of biological activities including anti-inflammatory [7], antimicrobial [8,9], antioxidant [10], anti-Alzheimer [11], analgesic [12] and anticancer effects [13][14][15]. In addition, some studies have shown that caffeic acid esters have high anti-leishmanial activity [16][17][18][19].…”
Section: Subgenus) As Well As L Mexicana and L Amazonensis (Membermentioning
confidence: 99%
“…Unfortunately, most of the synthesized compounds 4 and 5 did not demonstrate any antiradical activity against DPPH. Only compounds 4e and 4f exhibited a weak scavenging activity against DPPH; unfortunately, the antiradical activity of imine containing substituents exact as for protocatechuic aldehyde 4f was surprisingly low in comparison with other compounds containing moiety of 3,4-dihydroxybenzaldehyde, e.g., caffeic acid esters or their hydrogenated derivatives are well-known antioxidants [10], [11]. Also compounds 5c and 5d demonstrated a slight antiradical activity; their antiradical activity is nearly 50 % of the antiradical activity demonstrated by widely used antioxidant butylated hydroxytoluene (nearly 38 % [12]).…”
Section: Resultsmentioning
confidence: 99%